Disillusionment and Death in Ourika and “La Noire de...” - Rangarajan, Sudarsan (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
This study proposes to compare Claire de Duras’s Ourika (1824) and Ousmane Sembène’s “La Noire de...” (1962). The two novellas concern the assimilation of a Senegalese woman in the French society. Ourika is a young woman raised and educated in an aristocratic environment, while Diouana, the protagonist of Sembène’s story, who works as a maid, is illiterate. But the difference between the two women disappears as racism emerges. Using Fanon and Bhabha, this study focuses on the following aspects: Commodification and the loss of self; stigmatization and the protagonist as the Other; alienation and death; and suppressed voices and posthumous narratives. The essay concludes with a discussion of the significance of the struggles of the two protagonists, by extension, for Francophone African writers in the postcolonial context.